Budaya organisasi di Balai Diklat Industri Padang - Nurhaida Nasution Nasution; Ermita Ermita; Nurhizrah Gistituati; Lusi Susanti (Universitas Negeri Padang, 2022)
Abstract This research aims to obtain information about organizational culture at the Padang Industrial Training Center in terms of values ​​in terms of: trust, cooperation, responsibility, familiarity and openness. This research is descriptive research. The population of this study were all employees at the Padang Industrial Training Center, totaling 39 employees (population research). The instrument used was a Likert scale model questionnaire that had been tested to see its validity and reliability. Data were analyzed using the mean (average) formula. The result of this research is the organizational culture at the Padang Industrial Training Center, seen from the value of (1) trust gets an average score of 4.02 (2) cooperation. Gets an average score of 4.01 (3) responsibility gets. score. average 3.92 (4) familiarity got. average score 3.76 (5) openness got an average score of 3.9. So the Organizational Culture at the Padang Industrial Training Center is in the good category with an average score of 3.92